THE EFFECT OF LEADERSHIP, ORGANIZATIONAL CLIMATE, AND EMPLOYEE MOTIVATION OF PT DELTA MERLIN DUNIA TEXTILE VII - Palupi, Dyah Ayu Puri; Cahjono, Mardanung Patmo; Suprayitno (jfpublisher, 2023)
There are several problem statements of this research such as analyzing the effect of organizational climate, leadership, and employee motivation of PT Delta Merlin Dunia Textile VII. The population of this research involve the whole employees of PT Delta Merlin Dunia Textile VII with total of 30 people. This research used saturated sample which means that this sample is using all population people as a sampling technique. The analytical method in this research used instrument testing, classic assumption test, multiple linear analysis, T-test, F-test, and R2 test. The research result of multiple linear regression analysis indicated that leadership variable and motivation have a positive and significant effect on the employee performance, meanwhile organizational climate have a positive but not signifant effect on the employee performance of PT Delta Merlin Dunia Textile VII. The results of the Adjusted R Square coefficient of determination obtained the Adjusted R Square determination coefficient score around of 0.799 which means that the influence exerted by leadership, organizational climate, employee motivation is 79.9% while the remaining 20.1% is influenced by other variables which not included in this research, such as compensation, work environment, discipline.